Pengaruh Budaya Organisasi dan Lingkungan Kerja Terhadap Komitmen Organisasi Pada PT. Tahta Sukses Abadi Medan - Clarissa Daslim; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
PT. Tahta Sukses Abadi Medan, better known as the Brastagi Supermarket, the former Tiara Hotel. Organizational commitment is still not optimal, indicated by the presence of recapitulation data on employee attendance which is still low, the lack of employee desire to work well. An unsupportive physical work environment such as piling up files that are not neatly organized, work equipment and work equipment that are not supportive because some have been damaged. Regarding the organizational culture which has the motto of working with the nature of "Honest, Sincere, and Sincere" in reality, many employees do not use their working time effectively. This research uses quantitative descriptive research. The total population in the study was 98 employees with a sampling technique using a saturated sample. Simultaneously there is a significant influence between organizational culture and work environment variables on the organizational commitment of employees of PT. Tahta Sukses Abadi. While partially found organizational culture variables have a significant effect on the organizational commitment of employees of PT. Tahta Sukses Abadi. Partially it was found that the work environment variable had a significant effect on the organizational commitment of the employees of PT. Tahta Sukses Abadi.